Retrospective Analysis of Feline Ocular Diseases: Insights into Prevalence, Breed Predispositions, and Anatomical Localizations in a Veterinary Hospital in the Northeastern Anatolian Region of Turkey: 310 Cases (2016-2023) - Gölgeli Bedir, Ayşe; Yanmaz, Latif Emrah; Okur, Sıtkıcan; Şenocak, Mümin Gökhan; Turgut, Ferda; Kocaman, Yakup; Orhun, Ömer Tarık; Ersoz, Ugur; Doğan, Elif; Okumuş, Zafer; Baykal, Büşra (Erciyes Universitesi, 2024)
In this retrospective investigation, the medical records of feline patients exhibiting ocular symptoms were comprehensively collected from Atatürk University, Veterinary Faculty, Animal Hospital over the period ranging from 2016 to 2023. A complete investigation was carried out a total of 427 cases with ocular disease observed in 310 cats. A statistical analysis was made to identify patterns associated with breed, age, gender, and anatomical localization. No evidence of gender predisposition to ocular diseases was found, while a higher incidence was noted in kittens aged 0-6 months, resulting in 57.4% of cases. In relation to breed predisposition, it was observed that ocular diseases demon-strated a higher prevalence among Mix breed and British shorthair cat breeds. The predominant conditions observed within patients were adnexa diseases, which represented 50.2% of cases, followed by nasolacrimal system disorders, which represented 27.9% of cases. In summary, it was shown that brachycephalic breeds presented a higher preva-lence of nasolacrimal disorders, whereas mix breed breeds indicated a higher incidence of ocular diseases.
Keywords: Veterinary Surgery; Adnexa; British shorthair; cat; eye; nasolacrimal; Veteriner Cerrahi; British shorthair; göz; göz kapakları; kedi; nasolakrimal